A cruise to die for : an Alix London mystery - Elkins, Charlotte (Elkins, Charlotte. Alix London mystery, 2013)
This should be the cushiest job Alix London's ever had. The second Alix London mystery finds the art restorer in a world brimming with idle luxury, spectacular locations, and deadly intrigue. Surrounded by art and wealth and the sun-drenched Greek isles, she's aboard a sumptuous mega-yacht with no responsibilities save the occasional lecture to the guests of her temporary employer, Panos Papadakis, one of the world's richest men.